Penguatan Pendidikan Karakter dalam Implementasi Kurikulum Merdeka: Kajian Literatur - Ria Agustina; Agustina Agustina; Novia Juita; Edo Yuliandra Pratama (Departement of Mathematics Education, 2024)
The purpose of this research is to examine the strengthening of character education in the implementation of the independent curriculum. With the Systematic Literature Review approach, it can provide information on whether schools have understood the independent curriculum, what are the obstacles faced by schools, and whether the Pancasila student profile has been implemented so that it becomes the character education of the whole student. This study examines 5 articles on strengthening character education in the implementation of the independent curriculum. From the results of the SRL, it can be concluded that strengthening character education in the implementation of the independent curriculum has obstacles, among others, not fully understanding the essence of